THE IMPACT OF PLANT-BASED AND PLANT-RICH DIETS ON MACRONUTRIENT AND MICRONUTRIENT DEMAND AND FETAL HEALTH: A REVIEW - Agata Białek; Magdalena Mendak; Anna Hanslik; Monika Klimczak; Aleksandra Woskowska; Magdalena Domisiewicz (International Journal of Innovative Technologies in Social Science, 2025)
Introduction and purpose: Vegetarian and vegan diets are increasingly adopted by women of reproductive age due to their potential health and environmental benefits. However, pregnancy places higher nutritional demands on the body, and plant-based diets may increase the risk of certain nutrient deficiencies if not properly managed. This review explores the impact of vegetarian diets on maternal and neonatal outcomes. Evidence suggests that strict vegetarian diets are associated with lower birthweights and a higher incidence of small for gestational age (SGA) infants, although results vary between studies. Vegetarian mothers generally gain less weight during pregnancy and may be more likely to initiate and maintain breastfeeding. No consistent differences were observed in the rates of gestational diabetes, preeclampsia, or preterm birth across dietary groups. Nutrients of concern include vitamin B12, iron, vitamin D, calcium, DHA, zinc, and iodine. With appropriate dietary planning and supplementation, vegetarian and vegan diets can support healthy pregnancies and positive maternal and infant outcomes.Material and Methods: A comprehensive literature review was conducted using the PubMed and GoogleScholar databases, focusing on articles published since 2020. The search included the keywords: “vegetarian diet”, “pregnancy”, “pregnancy and diet” in various combination.Results: Strict vegetarian diets in pregnancy are often linked to lower birthweights and a higher risk of small for gestational age (SGA) infants, though results varied across studies. Vegetarian mothers generally gained less weight during pregnancy, with some showing a risk of inadequate weight gain. Strict vegetarians also showed higher breastfeeding initiation and longer duration. Nutrient deficiencies, particularly in vitamin B12, iron, vitamin D, calcium, DHA, zinc, and iodine were more common in vegetarian women, underlining the need for proper supplementation.Conclusions: Vegetarian and vegan diets can be safely followed during pregnancy, but they require careful nutritional planning and appropriate supplementation. While these diets may offer certain benefits such as healthier weight gain and better breastfeeding outcomes—they are also associated with potential risks, including lower birthweights and nutrient deficiencies. Key nutrients like vitamin B12, iron, vitamin D, calcium, DHA, and zinc must be closely monitored to support both maternal health and optimal fetal development.